Developmental activities and perceptions of challenge for National and Varsity women soccer players in Canada. (July 2019) - Hendry, David T.; Williams, A. Mark; Ford, Paul R.; Hodges, Nicola J.
Abstract: Objectives: Our aim was to assess the developmental activities that best define elite players in female soccer in one of the top nations for female soccer in the world. In addition to measurement of career practice hours in soccer and other sports, we quantified hours engaged in activities judged high in challenge. Design and Methods: Adult National-team ( n  = 21) and lesser-skilled Varsity ( n  = 24) female soccer players in Canada provided career estimates of hours in soccer and other sports during childhood and adolescence. Subjective ratings of challenge were provided for each activity across development, providing an indication of practice quality. Results: Both groups engaged in more coach-led soccer activities (practice, competition) than soccer play and spent the majority of their time in childhood in soccer compared to other sports. National players participated in more play that was more challenging and engaged in more moderate to high challenge practice, when compared to Varsity players. Conclusions: The importance of early engagement in soccer specific developmental activities for elite female soccer players in Canada was highlighted, as previously reported in male players. However, hours in soccer play during childhood were low in both groups and were lower than estimates from male players. Although the data do not fit squarely with any one pathway, they are mostly consistent with an early specialization route. Highlights: National & Varsity women soccer players competing at the highest levels took part. Elite groups were distinguished by childhood self-directed play not practice. Relative to practice hours and to men, hours in play were low (<25% in childhood). National players engaged in more hours of soccer activities rated challenging. Like male players, women started young and showed majority engagement in soccer.